2005
DOI: 10.1086/428089
|View full text |Cite
|
Sign up to set email alerts
|

Multitemperature Blackbody Spectrum of a Thin Accretion Disk around a Kerr Black Hole: Model Computations and Comparison with Observations

Abstract: We use a ray-tracing technique to compute the observed spectrum of a thin accretion disk around a Kerr black hole. We include all relativistic effects such as frame-dragging, Doppler boost, gravitational redshift, and bending of light by the gravity of the black hole. We also include self-irradiation of the disk as a result of light deflection. Assuming that the disk emission is locally blackbody, we show how the observed spectrum depends on the spin of the black hole, the inclination of the disk, and the torq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
470
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(476 citation statements)
references
References 58 publications
5
470
1
Order By: Relevance
“…1, the adopted accretion disk model assumes a non-rotating BH, although the chosen value of the radiation efficiency, η = 0.1, is above the maximum efficiency for a Schwarzschild BH. However, using the Li et al (2005) software package, Calderone et al (2013) found that the Shakura & Sunyaev (1973) model with R = 3R S , as used here, mimics the SED for an optically thick, geometrically thin accretion disk around a Kerr BH quite well with a spin parameter a 0.7, corresponding to a maximum radiative efficiency η = 0.1. For this choice of η our BH mass estimates are therefore affected little by having neglected the general relativistic effects associated with a Kerr BH.…”
Section: Sed Modelingmentioning
confidence: 85%
“…1, the adopted accretion disk model assumes a non-rotating BH, although the chosen value of the radiation efficiency, η = 0.1, is above the maximum efficiency for a Schwarzschild BH. However, using the Li et al (2005) software package, Calderone et al (2013) found that the Shakura & Sunyaev (1973) model with R = 3R S , as used here, mimics the SED for an optically thick, geometrically thin accretion disk around a Kerr BH quite well with a spin parameter a 0.7, corresponding to a maximum radiative efficiency η = 0.1. For this choice of η our BH mass estimates are therefore affected little by having neglected the general relativistic effects associated with a Kerr BH.…”
Section: Sed Modelingmentioning
confidence: 85%
“…The calculation of the thermal spectrum of a thin accretion disk has been extensively discussed in the literature; see e.g. Li et al (2005) and references therein for the Kerr case, and Bambi & Barausse (2011a), Chen & Jing (2012a) and Bambi (2012f) for a background with generic deviations from the Kerr solution. The spectrum can be conveniently written in terms of the photon flux number density as measured by a distant observer, N E obs .…”
Section: Continuum-fitting Methodsmentioning
confidence: 99%
“…Scaling this value up to a rotation of 581 Hz gives a * ≃ 0.27. To test whether the direct disc emission in the spectrum of 4U 1636-53 is significantly affected by relativistic effects we tried, instead of the diskbb, a multi-temperature blackbody model for a thin, general relativistic accretion disc in a Kerr metric, which also includes self-irradiation (kerrbb; Li et al 2005). However, using the kerrbb, assuming a distance of 6.5 kpc, a NS mass of 1.4 M⊙, and a * = 0.27, did not significantly improve the fit.…”
Section: Direct Emissionmentioning
confidence: 99%